Jet ventilation for the extraction of endobronchial foreing body in a patient with drained pneumothorax: A case report☆. Issue 2 (April 2017) - Latorre, Julieta; Brogly, Nicolas; Maggi, Genaro; Quinteros, Fabiola; del Ser, Natalia Peña; Gilsanz, Fernando
ABSTRACT : Introduction: : Even though foreign body aspiration (FBA) is rare in adult patients, they sometimes require the performance of rigid bronchoscopy for its extraction. Ventilation for this procedure is challenging, especially in patients with pulmonary disease. Clinical, diagnostic evaluation and interventions: : We described the case of a 71‐year old man who presented with a FBA in the left upper lobe associated with a controlateral pneumothorax. After the placement of a pleural drainage, the foreign body was extracted, using rigid bronchoscopy under general anesthesia and high flow jet ventilation with no further hemodynamic or pulmonary complications, suggesting that this technique is safe in patients with pulmonary leaks. Conclusion: : In the case described, rigid bronchoscopy minimized the risk of aspiration of blood and detritus due to continuous flow of gas upward, and avoided the increase of the air leak through the pneumothorax thank to limited airway pressures, making it a clear indication. Ventilación jet para la extracción de un cuerpo extraño endobronquial en un paciente con neumotórax drenado: informe de caso: RESUMEN: Introducción: : Aunque la aspiración de cuerpos extraños es rara en adultos, requiere en algunas ocasiones la realización de una broncoscopia rígida para su extracción. El modo ventilatorio para este procedimiento es un reto, especialmente en pacientes con enfermedad pulmonar. Clínica, evaluación diagnóstica e intervenciones: : Describimos aquí el caso de un paciente de 71 años con aspiración de un cuerpo extra ño enclavado a nivel del lóbulo superior izquierdo asociado a un neumotórax contralateral. Después de insertar un tubo de tórax se extrajo el cuerpo extraño utilizando broncoscopia rígida bajo anestesia general y ventilación jet de alto flujo sin complicaciones hemodinámicas o pulmonares adicionales, sugiriendo que esta técnica es segura en pacientes con fugas pulmonares. Conclusiones: : En el presente caso clínico, la broncoscopia rígida minimizó el riesgo de aspiración de sangre y detritus gracias a la inyección de un flujo continuo de gas ascendente, y evitó así el incremento de la fuga a través del neumotórax por las presiones limitadas en la vía aérea, constituyendo una indicación clara de esta técnica.